Virulence attenuation of Streptococcus pneumoniae clpP mutant by sensitivity to oxidative stress in macrophages via an NO-mediated pathway - Park, Chul-Yong; Kim, Eun-Hye; Choi, Sang-Yoon; Tran, Thao Dang-Hien; Kim, In-Hye; Kim, Su-Nam; Pyo, Suhkneung; Rhee, Dong-Kwon (MICROBIOLOGICAL SOCIETY KOREA, 2010)
ClpP protease is essential for virulence and survival under stress conditions in several pathogenic bacteria. The clpP mutation in a murine infection model has demonstrated both attenuation of virulence and a sensitivity to hydrogen peroxide. However, the underlying mechanisms for these changes have not been resolved. Because macrophages play a major role in immune response and activated macrophages can kill microbes via oxygen-dependant mechanisms, we investigated the effect of the clpP mutation on its sensitivity to macrophage-mediated oxygen-dependant mechanisms. The clpP mutant derived from D39 (serotype 2) exhibited a higher sensitivity to oxidative stresses such as reactive oxygen intermediates, reactive nitrogen intermediates, and H2O2, but no sensitivity to osmotic stress (NaCl) and pH. Moreover, viability of the clpP mutant was significantly increased in murine macrophage cells by treatment with S-methylisothiourea sulfate, which inhibits inducible nitric oxide synthase (iNOS) activity and subsequently elicits lower level secretions of nitric oxide (NO). However, viability of wild type was unchanged. Taken together, these results indicate that ClpP is involved in the resistance to oxidative stresses after entrapment by macrophages and subsequently contributes to virulence via NO mediated pathway.
Keywords: NITRIC-OXIDE; GENE-EXPRESSION; HEAT-SHOCK; INFECTION; PROTEINS; PROTEASE; NECROSIS; IDENTIFICATION; PROTECTION; MUTATIONS